Hemispatial neglect and serial order in verbal working memory. Issue 2 (9th January 2018) - Antoine, Sophie; Ranzini, Mariagrazia; van Dijck, Jean‐Philippe; Slama, Hichem; Bonato, Mario; Tousch, Ann; Dewulf, Myrtille; Bier, Jean‐Christophe; Gevers, Wim
Abstract : Working memory refers to our ability to actively maintain and process a limited amount of information during a brief period of time. Often, not only the information itself but also its serial order is crucial for good task performance. It was recently proposed that serial order is grounded in spatial cognition. Here, we compared performance of a group of right hemisphere‐damaged patients with hemispatial neglect to healthy controls in verbal working memory tasks. Participants memorized sequences of consonants at span level and had to judge whether a target consonant belonged to the memorized sequence (item task) or whether a pair of consonants were presented in the same order as in the memorized sequence (order task). In line with this idea that serial order is grounded in spatial cognition, we found that neglect patients made significantly more errors in the order task than in the item task compared to healthy controls. Furthermore, this deficit seemed functionally related to neglect severity and was more frequently observed following right posterior brain damage. Interestingly, this specific impairment for serial order in verbal working memory was not lateralized. We advance the hypotheses of a potential contribution to the deficit of serial order in neglect patients of either or both (1) reduced spatial working memory capacity that enables to keep track of the spatial codes that provide memorized items with a positional context, (2) a spatial compression of these codes in the intact representational space.